IDENTIFIKASI FORMALIN PADA BEBERAPA JENIS IKAN ASIN DENGAN MENGGUNAKAN METODE FEHLING A DAN FEHLING B DI PUSAT PASAR KOTA MEDAN TAHUN 2021 - M B Vista Laia; Dyna Grace Romatua Aruan (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2021)
Dried fish is a result of the salting and drying process. Low water content in salted fish is due to absorption by salt and evaporation caused by heat from the sun. There are several types of food that are added with additives that are prohibited from being added to food so that the food is more durable and looks better. Food ingredients that use food additives that are not in accordance with the provisions have a direct influence on the degree of human health. Formalin is not a food additive and is prohibited from being added to food. The purpose of the study was to identify the presence or absence of formalin in several types of salted fish which are traded in the market center of Medan city using the Fehling A and Fehling B methods. The place of this research was carried out in the chemical laboratory, USM Indonesia Medan. In the results of research that has been carried out on 20 samples of salted fish, it shows that salted fish samples with codes F5 and F12 contain formalin. The sample codes F5 and F12 gave a red precipitate after being heated which previously added 1 mL of Fehling A and Fehling B and 18 other samples did not show a red precipitate. After observing all samples, there were 2 samples that were positive for formalin from 20 samples of salted fish studied which were declared ineligible in the Regulation of the Minister of Health of the Republic of Indonesia NO.722|MENKES|PER|IX|88 concerning food additives.